A study on the technical vocational skills mismatch in Southern Mindanao (Region XI) - Quintana, Retzelyn Mae G.
The objective of the study was to assess the current status of Technical Vocational Education and Training (TVET) sector in Southern Mindanao (Region XI). It analyzed the demand and supply level of TVET in the region. Demand for TVET comes into two: demand of industries for tech-voc skills in the region, and the demand of students for TVET programs. Likewise, supply of TVET is identified according to the number of TVET graduates and the number of TVET providers in Region XL Primary and secondary data analyses were employed in the research. Secondary data were gathered from National Statistics Office (NSO). National Statistical Coordination Board (NSCB) and TESDA XI, and TESDA Davao City/Sur Provincial Office. Key informant interviews were conducted among TVET enrollees, TVET providers, and TVET user or firm utilizing TVET skills to identify key issues and policies. From the gathered data, the skills mismatch in Southern Mindanao was determined. Results showed that construction and carpentry skills are currently in-demand in Davao City and Davao del Sur. However, a large a number of TVET graduates were products of Security (In-Service) and Related Courses and Computer Related Programs. Thus, this created skills mismatch in the area. The study recommends that reliable and on-time market information studies should be conducted to inform TVET enrollees of skills prioritized by industries for the current and future years. Moreover, enough government support is also needed by TVET institutions, particularly the public TVIs, to improve TVET provision in Southern Mindanao.